Atlas of Challenges and Opportunities in European Neighbourhoods - Beckouche, Pierre; Besnard, Pierre; Pecout, Hugues (Springer International Publishing : Imprint: Springer, 2016)
This atlas provides a macro-regional overview of the areas that surround the European Union, from the Sahara to the Middle East, Western Balkans to European Russia, Turkey to the Arctic. Detailing key socio-economic data as well as developmental trends, the maps provide a comprehensive territorial analysis at a local scale and explore the potential for regional integration and cooperation. These pioneering maps examine challenges that threaten this wide, yet inter-connected, region, including environmental concerns in the North, political unrest in the East, social factors in the Western Balkans, and the upheaval in the Mediterranean since the Arab spring. Coverage investigates such key countries and areas as Libya, Israel, Palestine, Syria, and the Ukraine as well as explores such essential issues as Europe’s energy procurement. In addition, it also presents a comparison with other world regions such as East Asia and North America. In the end, readers discover that territorial integration faces many shortcomings, but that deep regional cooperation would be a key driver for the EU’s sustainable future. This atlas features the main results of the “Integrated Territorial Analysis of the Neighbourhoods” research project undertaken by ESPON (The European Observation Network for Territorial Development and Cohesion). It provides scholars; local authorities and NGOs involved in cross-border cooperation; companies interested in energy, agriculture, water, transportation and communication; and interested readers with key insights into this important region.